Perceived barriers and facilitators to health behaviors in European childhood cancer survivors: a qualitative PanCareFollowUp study - Bouwman, Eline; Pluijm, Saskia M. F.; Stollman, Iridi; Araújo-Soares, Vera; Blijlevens, Nicole M. A.; Follin, Cecilia; Winther, Jeanette F.; Hjorth, Lars; Kepak, Tomas; Kepakova, Katerina; Kremer, Leontien C. M.; Muraca, Monica; et al. (Cancer medicine, 2023)
Background Healthy behaviors, that is, engaging in regular physical activities, maintaining a healthy diet, limiting alcohol consumption, and avoiding tobacco and drug use, decrease the risk of developing late adverse health conditions in childhood cancer survivors. However, childhood cancer survivors may experience barriers to adopting and maintaining healthy behaviors. This study aimed to assess these barriers and facilitators to health behavior adoption and maintenance in childhood cancer survivors. Methods A focus group ( n = 12) and semi-structured telephone interviews ( n = 20) were conducted with a selected sample of European and Dutch childhood cancer survivors, respectively. The Theoretical Domains Framework (TDF) was used to inform the topic guide and analysis. Inductive thematic analysis was applied to identify categories relating to barriers and facilitators of health behavior adoption and maintenance, after which they were deductively mapped onto the TDF. Results Ten TDF domains were identified in the data of which “Knowledge,” “Beliefs about consequences,” “Environmental context and resources,” and “Social influences” were most commonly reported. Childhood cancer survivors expressed a need for knowledge on the importance of healthy behaviors, possibly provided by healthcare professionals. They indicated physical and long-term benefits of healthy behaviors, available professional support, and a supporting and health-consciously minded work and social environment to be facilitators. Barriers were mostly related to a lack of available time and an unhealthy environment. Lastly, (social) media was perceived as both a barrier and a facilitator to healthy behaviors. Conclusion This study has identified education and available professional support in health behaviors and the relevance of healthy behaviors for childhood cancer survivors as key opportunities for stimulating health behavior adoption in childhood cancer survivors. Incorporating health behavior support and interventions for this population should therefore be a high priority.
Online veröffentlicht: 7. April 2023
Gesehen am 19.06.2024